Kreativitas guru dalam proses pembelajaran ditinjau dari penggunaan metode pembelajaran jarak jauh di tengah wabah COVID-19 - Ida Yeni Rahmawati; Dwiana Binti Yulianti (Universitas Muhammadiyah Ponorogo, 2020)
Corona Virus Disease (COVID-19) had an impact on various fields, especially in education. The existence of this pandemic requires everyone to not be able to carry out his normal activities as before. In the education field, the teaching-learning process cannot be done directly in the classroom. Therefore, the teaching process is inverted by distance teaching (online). Distance teaching is done to reduce the spread of COVID-19 among students and the community. This research is library research that aims to explain creativity in the application of distance teaching. This research is library research conducted by reading and recording various literature or reading materials that are in accordance with the subject matter. The results of this study indicated that distance teaching requires a practical and attractive framework so that the students can participate in learning enthusiastically. Distance teaching is very effective and efficient but teachers have limitations in controlling the value of students’ character education directly. Distance teaching has an impact on parents and teachers because parents have to provide additional costs for purchasing internet quota. On the other hand, for teachers, not all teachers are proficient in using technology and social media as learning media. The results of the study are expected to be able to consider for teachers in doing distance teaching during COVID-19.